A New Paradigm of Islamic Womanhood in Liala Aboulela's Minaret and Shelina Janmuhmmed's Love in a Headscarf - Azhar Hameed mankhi, Assistant professor (Journal of College of Education, 2021)
This paper emphasizes Muslim women's voices in their search for religious freedom as well as their attempts to assert their religious identity in the secularized western society .I aim to discuss two novels by two literary Muslim women writers: Laila Aboulela's Minaret ( 2005)and Shelina Janmuhammed's Love in a Head scarf (2009). These two writers refuse to see Islam in a western eye ,and they refuse the many labels and stereotypes of Muslim women who live in a secularized society. They both agree that Islam as an instrument of empowerment in the life of Muslim female characters living in Europe. They present a new image of Muslim woman whose religion frees her of all the cultural and societal traditions .